Is There BN Bond‐Length Alternation in 1, 2:3, 4:5, 6‐Tris(biphenylylene)borazines?. Issue 9 (17th May 2013) - Müller, Matthias; Maichle‐Mössmer, Cäcilia; Sirsch, Peter; Bettinger, Holger F.
Abstract The alternation of the BN bonds in the central borazine ring of the overcrowded 1, 2:3, 4:5, 6‐tris(biphenylylene)borazine (2 a) and its tribromo derivative (2 g) is investigated by computational methods and compared with their experimentally obtained crystal structures. The calculations are performed with a meta‐generalized‐gradient‐approximation (GGA) density functional (Tao–Perdew–Staroverov–Scuseria (TPSS)) without and with dispersion corrections, including Becke–Johnson damping, in conjunction with a polarized triple‐ζ basis set. These data show a small bond‐length alternation (BLA) of around 0.01 Å in 2 a and 2 g. This outcome is in good agreement with X‐ray diffraction data for 2 g, but at variance with earlier X‐ray diffraction measurements that gave a BLA of 0.06 Å for 2 a. A re‐investigation of the crystal structure of 2 a reveals a positional disorder that precludes a discussion of the BN bond lengths. The synthesis of 2 g is the first example of an electrophilic aromatic substitution of an aryl borazine with elemental bromine. Successful bromination was also demonstrated for hexaphenylborazine.